Mapping the viral sequences conferring leukemogenicity and disease specificity in Moloney and amphotropic murine leukemia viruses. - DesGroseillers, L (1984)
The Moloney murine leukemia virus (MuLV) is a highly leukemogenic virus. To map the leukemogenic potential of Moloney MuLV, we constructed chimeric viral DNA genomes in vitro between parental cloned infectious viral DNA from Moloney and amphotropic 4070-A MuLVs. Infectious chimeric MuLVs were recovered by microinjection of recombinant DNA into NIH/3T3 cells and tested for their leukemogenic potential by inoculation into NIH/Swiss newborn mice. Parental Moloney MuLV and amphotropic 4070-A MuLV induced thymic and nonthymic leukemia, respectively, when inoculated intrathymically. With chimeric MuLVs, we found that the primary determinant of leukemogenicity of Moloney and amphotropic MuLVs lies within the 1.5-kilobase-pair ClaI-PvuI long terminal repeat (LTR)-containing fragment. The presence of additional Moloney env-pol sequences with the Moloney LTR enhanced the leukemogenic potential of a chimeric MuLV significantly, indicating that these sequences were also involved in tumor development. Since parental viruses induced different forms of leukemia, we could also map the viral sequences conferring this disease specificity. We found that the 1.5-kilobase-pair ClaI-PvuI LTR-containing fragment of Moloney MuLV was necessary and sufficient for a chimeric MuLV to induce thymic leukemia. Similarly, the same LTR-containing fragment of amphotropic MuLV was necessary and sufficient for a chimeric MuLV to induce nonthymic leukemia. Therefore, our results suggest that specific sequences within this short LTR-containing fragment determine two important viral functions: the ability to transform cells in vivo (leukemic transformation) and the selection of a specific population of cells to be transformed (disease specificity).